Anuric Acute Kidney Injury in Chronic Myeloid Leukemia: A Rare Complication Case - Angela Kimberly Tjahjadi; Artaria Tjempakasari (Acta Medica Indonesiana)
This report describes a rare case of anuric acute kidney injury related to suspected urate nephropathy in a 23-year-old male with chronic phase of Chronic Myeloid Leukemia (CML). The patient presented with anuria and limb edema, with a history of imatinib-treated CML. Investigations revealed probable urate crystals causing bilateral hydronephrosis and hydroureters. Management included fluid restriction to maintain euvolemic status, hypouricemic agents, urinary alkalinization, urgent hemodialysis for acute kidney injury, and blood product transfusions to address haematological imbalances. The continued use of imatinib and aforementioned treatments resulted in the restoration of renal function depicted through normalization of serum urea, creatinine and uric acid levels. This case highlights the importance of meticulous assessment and management of anuric acute kidney injury in CML patients to ensure a positive outcome.